The Impact of Leadership Management and Organizational Culture on the Success of Business Marketing Management in Socio-Economic Development - Doddy Adhimursandi; Abdul Rauf; Erwin Setiawan; Arvita Rachmawaty (Mimbar Ilmu, 2025)
The lack of contribution of the business marketing sector in micro, small, and medium enterprises (MSMEs) to economic development. The urgency of this research lies in the need to strengthen internal factors, particularly leadership and organizational culture, so that MSMEs can compete. The purpose of this study is to analyse the influence of marketing management, leadership, and organizational culture in business marketing on the success of MSME marketing management. This study uses a quantitative approach with logistic regression analysis. The sample consisted of 533 MSME actors selected through a total sampling technique. Data were collected through questionnaires, observation, and documentation, then analysed using SPSS version 29.0. The results show that leadership has a significant effect on the success of business marketing management leadership, with a coefficient value of 2.157, and business marketing organizational culture of 1.934. Simultaneously, both explain 82.1% of the variation in the success of MSME marketing management. The findings indicate that transformative leadership and a collaborative culture create an innovative and productive work environment. In conclusion, the synergy between effective marketing management leadership and a strong marketing organizational culture is a major factor in the success of MSME marketing. The implications of this research emphasize the importance of leadership training and strengthening an adaptive organizational culture to increase competitiveness and sustainability of the social economy globally.